Outpatient COVID-19 with telemedicine follow-up - Pedretti, Ana S.; Grande Ratti, María F. (Revista del Hospital Italiano de Buenos Aires, 2022)
As a result of this publication, we take the opportunity to review the enormous challenge of the COVID-19 pandemic in the Emergency Department. We comment the effort, dedication and work (behind the scenes) throughout the route, and our experience of outpatient follow-up with telemedicine.
Keywords: emergency medical services; coronavirus infections; ambulatory care; telemedicine